Demand for Oil Products in OPEC Countries: A Panel Cointegration Analysis - Yousef, Nourah Al (International Journal of Energy Economics and Policy, 2013)
The increasing consumption of oil-refined products on OPEC countries will have its impact on the availability of oil exports. The goal of this paper is to examine the determinants of oil refined products’ consumption for a panel consisting of 7 OPEC countries, namely, Algeria, Kuwait, Libya, Qatar, Saudi Arabia, United Emirates and Iran for the period of 1980–2010, by employing the recently developed panel data unit root tests and panel data cointegration techniques. Furthermore, conditional on finding cointegration, the paper extends the literature by employing the Pedroni Panel Fully Modified Ordinary Least Squares (FMOLS) Dynamic OLS (DOLS) procedure to generate. The study estimates the demand for Gasoline, Kerosene and Diesel. An attempt is also made to assess the impact of this demand on the future availability of OPEC oil exports. Keywords: OPEC; Demand for Gasoline; Kerosene; Diesel; Cointegration; panel data JEL Classifications: C33; Q41; Q43